2017
DOI: 10.1183/13993003.01140-2017
|View full text |Cite
|
Sign up to set email alerts
|

How effective is bronchial thermoplasty for severe asthma in clinical practice?

Abstract: @ERSpublications Bronchial thermoplasty can be effective in patients who often have features of more severe asthma than in AIR2 http://ow.ly/Qv5730cTIuBCite this article as: Thomson NC, Chanez P. How effective is bronchial thermoplasty for severe asthma in clinical practice? Eur Respir J 2017; 50: 1701140 [https://doi.org/10.1183/13993003.01140-2017.Bronchial thermoplasty is an intervention developed for the treatment of asthma through the delivery of radio frequency energy to the airways [1,2]. Evidence for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Nevertheless, the data were prospectively collected and similar between two academic centres. Furthermore, the clinical benefit was sustained and similar to previous reports . Given the substantial sample size in the current study, the authors feel that it is unlikely that further studies using oscillometry will shed light on the effects of BT.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, the data were prospectively collected and similar between two academic centres. Furthermore, the clinical benefit was sustained and similar to previous reports . Given the substantial sample size in the current study, the authors feel that it is unlikely that further studies using oscillometry will shed light on the effects of BT.…”
Section: Discussionsupporting
confidence: 88%
“…As has been observed in previous studies, spirometry did not change despite the demonstrated clinical improvement. Although the mechanisms have not been clearly defined, one suggestion is that BT might be inducing physiological changes in the small airways—the zone of the lung that is inadequately assessed by spirometry .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in most studies of BT, patients exhibit significant clinical improvement without any improvement in FEV 1. [17][18][19] This suggests that we may have been looking in the wrong place in attempting to understand how BT works. It is well established that spirometry predominantly measures airway resistance in the larger airways.…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that ASM is simply a vestigial tissue with no significant function in highly evolved mammals (154,155). This argument was one of a number used to promote the concept of thermoplasty and muscle destruction as a potentially safe approach to the treatment of asthma (156)(157)(158).…”
Section: What Is the Role Of Asm If Any In Healthy Airways?mentioning
confidence: 99%